Effects of Picture References on Reproducibility of Entheseal Change Recordation - (:unkn) unknown (My University, 2020)
Reproducibility and observer agreement are critical to the production of standardized and comparable data sets. The reproducibility of recording methodology is a current issue in entheseal change studies. The effects of a picture reference guide on current entheseal change methodology are explored in the hope of increasing observer agreement and thus overall applicability of the picture reference guide method in a variety of archaeological contexts. The picture guide seems marginally effective; however, it requires a few modifications and subsequent testing before full-scale implementation.
Keywords: Entheseal change; Schroeder Mounds